The accidental CIO a lean and agile playbook for IT leaders - Millett, Scott (Ascent Audio, 2024)
An indispensable guide showing IT leaders the way to balance the needs of innovation and exploration with exploitation and operational reliability. In The Accidental CIO, veteran software developer-turned-executive Scott Millett delivers an essential playbook to becoming an impactful, strategic leader at any stage of your IT leadership journey. You'll find a wealth of hands-on advice for tackling the many challenges and paradoxes that face technology leaders, from creating an aligned IT strategy, defining a target architecture, designing a balanced operating model, and leading teams and executing strategy.